The age of trespass. - Kuttner, Robert (American Prospect)
The writer discusses the attitude of the Right in the U.S. to what threatens and protects personal freedoms—particularly the right to privacy. He contends that the Right, despite its philosophy of small government as a safeguard of personal liberty, seems indulgent of the state's police power and of the current assault on liberty and privacy being made by private property itself in the form of the dissemination of personal data and information. He asserts that the European Union has shown itself to be more adept at handling personal information than the U.S. private sector and consequently has shown itself to be a better guardian of privacy. He concludes that the Right's attitude to property and privacy rights is based on its relationship with America's elite and puritanical conservatives.